Оценка финансовых методов использования капитала - Левина, Е.В.; Михальская, В.А.; Кравченко, В.В. (Інститут економіки промисловості НАН України, 2006)
Подано оцінку структури і джерел формування авансованого капіталу в економіці України за 2001-2004 рр., розкрито їх особливості на підприємствах різних видів промислової діяльності. Установлено невідповідність формування капіталу відомим з теорії управління структурою капіталу типом моделей, обумовлену особливостями сучасного етапу трансформації економіки.
---------- Дана оценка структуры и источников формирования авансированного капитала в экономике Украины за 2001-2004 гг., раскрыты их особенности на предприятиях различных видов промышленной деятельности. Установлено несоответствие формирования капитала известным из теории управления структурой капитала типом моделей, обусловленное особенностями современного этапа трансформации экономики.
---------- The structure and sources of advanced capital formation in the economy of Ukraine during 2007-2004 are estimated; their specific features are shown on the example of enterprises engaged in different production activities. The conclusion is made that formation of the capital doesn’t correspond to the type of models known from the theory of capital structure management, it is explained by specific features of the modern stage of the economy transformation.

----------